2019
DOI: 10.1177/8755122519872697
|View full text |Cite
|
Sign up to set email alerts
|

Team Communication on Tasks Performed in Blood Pressure Clinics in Community Pharmacies

Abstract: Background: To successfully deliver pharmacy services, pharmacists and technicians need to work as a team and have effective communication. Objectives: To measure the amount of communication between community pharmacists and their technicians during monthly blood pressure (BP) clinics. Methods: Cross-sectional survey method was used to assess the amount of communication pharmacists and technicians had on each task. Study participants were pharmacist-technician pairs (teams) from 10 intervention community pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…(24) . Favorable interaction between pharmacy members, can efficiently improve work processes and deal with unaccepted events that may occur during the daily work (25) . Constantly pharmacy team can communicate with patients and realize the causes that influence patients' ability to control their chronic disorders (26) .…”
Section: Discussionmentioning
confidence: 99%
“…(24) . Favorable interaction between pharmacy members, can efficiently improve work processes and deal with unaccepted events that may occur during the daily work (25) . Constantly pharmacy team can communicate with patients and realize the causes that influence patients' ability to control their chronic disorders (26) .…”
Section: Discussionmentioning
confidence: 99%
“…53 Another study from the United States that conducted semistructured interviews also reported that strong communication between pharmacy staff members was noted as an important element in successfully providing pharmaceutical services. 54 Because the favorable interaction between pharmacy members can efficiently improve work processes and the ability to deal with unexpected events, 55 community pharmacies must set up an effective handover communication system among their pharmacy staff members. Meanwhile, the PRR for "response to mistakes" indicates that we need to focus on high-level understanding to accept staff members' mistakes and appreciate feedback.…”
Section: Types Of Pharmacy Pharmacy Positionmentioning
confidence: 99%